Precipitation increase promotes soil organic carbon formation and stability via the mycorrhizal fungal pathway - Tangqing He; Yunfeng Zhao; Xiaodong Wang; Yunpeng Qiu; Jun Deng; Kangcheng Zhang; Xinyu Xu; Yexin Zhao; Kaiyun Qian; Hao Wang; Tongshuo Bai; Yi Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
Arbuscular mycorrhizal fungi (AMF) form symbiotic relationships with roots of most terrestrial plants, playing a crucial role in regulating soil organic carbon (SOC) dynamics. While precipitation increase (Pi) is a major facet of climate change, its impacts on root- and AMF-mediated SOC formation and stability remain largely unexplored. Here, we combined a meta-analysis across global grasslands with a multiyear precipitation manipulation experiment in a semiarid grassland on the Loess Plateau to disentangle the relative effects of roots and their associated AMF on microbial communities and SOC as influenced by Pi. We show that Pi induced tradeoffs between roots and AMF, and promoted SOC formation and stability via the mycelium- rather than the root-pathway, leading to an increase of 136% (±40) and 297% (±90) in mycelium-derived C and mineral-associated organic C (MAOC), respectively. Pi altered plant community composition, favoring subshrubs and forbs over grasses. Also, Pi reduced specific root length, but increased root diameter, tissue density, and root colonization and extraradical biomass of AMF. Furthermore, Pi-induced change in AMF shifted the soil bacterial community by favoring K-strategists, increasing bacterial necromass C and promoting MAOC accumulation. Our findings provide direct evidence that Pi enhances AMF-driven SOC sequestration by expanding the mycorrhizosphere and promoting microbiota with high C use efficiency, highlighting a key mechanism by which mycorrhizal fungi mediate SOC formation and stability under shifting precipitation regimes.